2018
DOI: 10.1186/s11671-018-2595-1
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Periodic Polystyrene Nanosphere Array Using the Dip-Drop Method with Post-deposition Etching and Its Application of Improving Light Extraction Efficiency of InGaN/GaN LEDs

Abstract: In this study, we synthesized a periodic polystyrene nanosphere (PS NS) array using the dip-drop method with post-deposition etching to improve the light extraction efficiency (LEE) of InGaN/GaN light-emitting diodes (LEDs). The dip-drop method has advantages such as simple procedure, inexpensive equipment, room temperature deposition, and easy implementation in LEDs. The arrangement of PS NSs on an indium-tin-oxide (ITO)-coated glass substrate depends on the average dip-drop speed and the concentration of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Moreover, controlling the process and achieving a high repeatability of the rough window layer are difficult tasks. Some studies have reported that photonic crystals [22] and nanopyramids [23] can increase the LEE of InGaN/GaN LEDs through either diffraction or resonant coupling. However, these approaches are not practical because they require technologies that can accurately control the dimension, such as e-beam lithography, which is not suitable for obtaining a high throughput.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, controlling the process and achieving a high repeatability of the rough window layer are difficult tasks. Some studies have reported that photonic crystals [22] and nanopyramids [23] can increase the LEE of InGaN/GaN LEDs through either diffraction or resonant coupling. However, these approaches are not practical because they require technologies that can accurately control the dimension, such as e-beam lithography, which is not suitable for obtaining a high throughput.…”
Section: Introductionmentioning
confidence: 99%